Case report: A case of Savolitinib in the treatment of MET amplification mutation advanced lung adenocarcinoma with rare bilateral breast metastasis - Deng, Rui; Li, Yan-ying; Bai, Liang-liang; Zhou, Li; Wang, Yong-Sheng (Frontiers in Oncology, 2024)
Background: The distant metastasis of lung cancer primarily occurs in the bones, liver, brain, and lungs, while the breast is an extremely rare site of metastasis. There is very limited literature on the occurrence of breast metastasis from lung cancer, and metastatic lesions in the breast are prone to being misdiagnosed as primary breast cancer, requiring careful attention and differentiation in the clinical diagnostic and treatment process. Case summary The patient, a 63-year-old female, initially presented with an EGFR exon 21 L858R mutated left lung adenocarcinoma in 2017, treated successfully with surgical resection and subsequent monitoring. The relapse of disease occurred in January 2020. Despite maintaining a prolonged progression-free survival (PFS) with first-generation EGFR-TKI Afatinib, disease progression occurred in 2022 without detectable resistance mutations. Transition to second-generation TKI Furmonertinib resulted in poor control, with rapid progression including unusual bilateral breast metastases that exhibited inflammatory breast cancer-like peau d'orange changes. Standard chemotherapy achieved only short-term stability. Upon detecting a MET amplification mutation, treatment with Savolitinib was initiated. Remarkably, this led to significant clinical and radiographic improvement, notably resolving the peau d'orange appearance and reducing multiple lesions across the body. Conclusion This case underscores the importance of continuous genetic profiling and tailored treatment approaches in managing advanced lung adenocarcinoma, particularly when presenting with rare metastatic sites and complex genetic landscapes. The successful application of Savolitinib following the identification of a MET amplification mutation highlights its potential in overcoming resistance mechanisms in NSCLC, providing a significant therapeutic option for similarly challenging cases.